Diabetic Ketoacidosis Associated with Sodium-Glucose Cotransporter 2 Inhibitors: Clinical and Biochemical Characteristics of 29 Cases - G. A. Stamatiades; P. D’Silva; M. Elahee; G. M. Viana; A. Sideri-Gugger; S. K. Majumdar (International Journal of Endocrinology)
Context. Numerous reports suggest an association between SGLT2 inhibitors and DKA. Since the use of these drugs for diabetes has increased dramatically, identification of patients at greatest risk of this life-threatening complication is essential. Objective. To describe the clinical and biochemical characteristics of all reported cases of DKA associated with SGLT2 inhibitor use in patients with type 2 diabetes mellitus and to identify potential risk factors. Design. A retrospective case series was conducted between March 2013 and August 2019 using an electronic medical record search algorithm. Results. 25 patients met the criteria for DKA associated with SGLT2i use (total of 29 cases), 15 were female, average age was 54.24 years, and mean diabetes duration was 8.76 years. The majority of the patients (23 patients) had no history of prior DKA. Average blood glucose concentrations at presentation were 298.9 ± 152.7 mg/dl. Interestingly, nearly half of the episodes (14) met the criteria of euglycemic DKA (glucose <250 mg/dl). Average anion gap values were 26.59 ± 6.15 mg/dl, bicarbonate values were 11.14 ± 5.57 mg/dl, and pH values were 7.16 ± 0.12. All had positive serum and urine ketones. The most common presenting symptoms were nausea, vomiting (18 cases), and abdominal pain (10 cases). Common precipitants were poor oral intake (18 cases) and infection (10 cases). A variety of drugs were prescribed along with an SGLT2i, and 11 of the patients were using insulin. None of the cases were fatal. Comparison between euglycemic DKA and hyperglycemic DKA did not identify any significant difference. A major limitation factor of the study was the lack of control group or comparison to other antiglycemic agents to assess the relative risk. Conclusions. The majority of SGLT2i-associated DKA cases occurred in patients with T2DM without prior episodes of DKA. The most common presenting symptoms were nausea, vomiting, and abdominal pain, while poor food intake and infection were the main precipitants. Clinicians should consider the possibility of DKA in SGLT2i-treated patients presenting with these symptoms, even in absence of marked hyperglycemia.